A cross-sectional study of impact of school environment on students’ health - Ram, Uppala S. S.; Rao, Yeluri S.; Gara, Himavathy K.; Rao, Vanamali D. (International Journal Of Community Medicine And Public Health, 2021)
Background: A child’s growth and personality depends not only on his intelligence but also emotional health which incorporates his family, peer, school and teachers. This study aimed to evaluate quality of life in school (QoLS) among school children aged 13-16 years and to explore their school environment. Methods: In this community-based study, 293 school children were randomly selected from an urban community and were subjected to face-to-face interviews to obtain: socio demographic features inclusive of age, gender and details of school; and QoLS instrument exploring psychosocial factors, attitude towards school, teacher-student relationship and school environment. Results: Males had 57.68% representation. Majority belonged to private schools (71.6%) and state board (92.83%). Majority confirmed for adequate lighting (97.27%), clean school (91.47%), and extra-curricular activities (85.32%). Few faced problems like teasing (19.79%), feeling unsafe (16.38%), and loneliness (13.99%). Majority were satisfied with teachers (92.15%) and found them supportive (96.58%) and approachable (91.47%). The lowest and highest QoLS scores were reported for psychosocial factors (3.335±0.991) and teacher-student relationship (3.645±0.773) respectively. Girls reported significantly higher scores for school environment. Residential and 8th grade students gave significantly higher scores for total QoLS and all domains. QoLS was not affected by the school being government or private and education board being state or CBSE. Conclusions: Teacher-students relationship and psychosocial factors were scored highest and lowest respectively in QoLS. Girls, younger age and residential students had higher perception of QoLS. To achieve transformative growth and healthy adulthood, both family and school should focus on safe, stimulating and supportive environment for the child depending on age and gender-specific needs.